Synthesis of tetrahydrofuro[3,2-c]pyridines via Pictet–Spengler reaction - Mendogralo, Elena Y.; Uchuskin, Maxim G. (Beilstein Journal of Organic Chemistry, 2023)
A semi-one-pot method for the synthesis of 4-substituted tetrahydrofuro[3,2-c]pyridines by the Pictet–Spengler reaction was developed. The method is based on the condensation of easily accessibly 2-(5-methylfuran-2-yl)ethanamine with commercially available aromatic aldehydes followed by acid-catalyzed Pictet–Spengler cyclization. Using this approach, we synthesized a range of 4-substituted tetrahydrofuro[3,2-c]pyridines in reasonable yields. The reactivity of some of the products was investigated and selected synthetic transformations of the obtained tetrahydrofuro[3,2-c]pyridines were shown.
Keywords: acid hydrolysis; 1,4-diketone; tetrahydrofuro[3,2-c]pyridines; Paal–Knorr reaction; Pictet–Spengler reaction